Baby Bear, Baby Bear, What do you See? - Martinm Bill; Carle, Eric (London Penguin Books Ltd, 2007)
Baby Bear meets all sorts of different animals until he finally finds what he is looking for - his mother. Told through Bill Martin's rhythmic text and Eric Carle's vibrant images, this is the fourth companion title to the much-loved classic Brown Bear Brown Bear, What Do You See?
English stories
2
Keywords: English stories